Home Automation System using Raspberry Pi - Gaudani, Hetal; Vora, Saurabh; Todarmal, Swati (IJRDO -Journal of Computer Science Engineering, 2015)
Nowadays automation encompasses many vital elements, systems and job functions. To embed this term with controlling devices especially for electric devices at home will give a system which will turn to be highly beneficial to end user. Therefore we have presented the architecture and implementation of the home automation system for controlling electric devices using raspberry pi as the central (main) hardware. The proposed system is having two parts; the first part consist web server controlling user interface and the details of the devices are stored in the database. While second part consists hardware structure which provides appropriate interface to raspberry pi and electric devices. This part also consist a controller module as a bridge between raspberry pi and electric devices. Unlike most of other available home automation system we have used raspberry pi as the main hardware due to benefits like low cost, high performance and massively diverse range of uses and applications